(untitled) (International Journal of Built Environment and Sustainability, 2022)
Understanding the public perceptions towards green infrastructure can be instrumental in identifying effective strategies for greening. This research focuses on the less exploited green boundary walls among the different green infrastructure options. A questionnaire survey was conducted among three hundred twenty-eight residents in residential areas of Colombo district, Sri Lanka, to understand the public perceptions that affect green urban boundary walls. Using Likert scales, participants expressed their perception of benefits and challenges related to greening boundary walls along with socio-economic data. Relaxation effects, improvement of aesthetic appearance, becoming close to nature, and improving air quality were among the highest-rated benefits. Lack of knowledge and time and money requirement was identified as significant challenges. Misconceptions about property damages and nuisance to the owner are demotivators for nearly 38% of the sample as determined by the cluster analysis. Interventions such as providing relevant knowledge on methods of green wall construction and maintenance methods and subsidies can be recommended. Raising awareness through pilot programs and opportunities for experience sharing may motivate people towards greening boundary walls. The study concludes with strategies applicable in motivating residents towards greening their boundary walls.